Accelerated Recovery of Endothelium Function after Stent Implantation with the Use of a Novel Systemic Nanoparticle Curcumin. (8th June 2015) - Lu, Qi; Ye, Fang; Yang, Xiangjun; Gu, Qingqing; Wang, Peng; Zhu, Jianhua; Shen, Li; Gong, Feirong
Abstract : Curcumin was reported to exhibit a wide range of pharmacological effects including antioxidant, anti-inflammatory, and antiproliferative activities and significantly prevent smooth muscle cells migration. In the present study, a novel kind of curcumin loaded nanoparticles (Cur-NP) has been prepared and characterized with the aim of inhibiting inflammation formation and accelerating the healing process of the stented arteries. Cur-NP was administrated intravenously after stent implantation twice a week and detailed tissue responses were evaluated. The results demonstrated that intravenous administration of Cur-NP after stent implantation accelerated endothelial cells restoration and endothelium function recovery and may potentially be an effective therapeutic alternative to reduce adverse events for currently available drug eluting stents.